Ephraim Radner, Hosean Wilderness, and the Church in the Post-Christendom West : A Dialogue on the Shape of Waiting - Erickson, Amy J., (Studies in Systematic Theology;, 2020)
Ephraim Radner, Hosean Wilderness, and the Church in the Post-Christendom West offers the first monograph-length treatment of the compelling and perplexing contemporary Anglican theologian Ephraim Radner. While unravelling his distinctive approach to biblical hermeneutics and ecclesiology, it queries the state of today's secularized church through a theological interpretation of an equally enigmatic writer: the prophet Hosea. It concludes that an eschatological posture of waiting and a heuristic of poesis should dictate the church's shape for an era in which God is stripping the church of its foregoing institutional forms.